Diagnosis of Difficulties in Learning Stoichiometry Based on College Students' Education Backgrounds - Raehanah Raehanah; Syarifatul Mubarak (Postgraduate, University of Mataram, 2025)
This study analyzed the learning difficulties in stoichiometry for university students at the Chemistry Department of UIN Mataram based on their upper secondary education backgrounds. This research employed a descriptive design with a quantitative approach. The sampling technique utilized was purposive sampling, targeting students who had studied stoichiometry. The research instrument was an open-ended diagnostic test form, which was validated by an expert. Data analysis techniques included calculating the percentages of question indicator completeness. The results indicated that the stoichiometric learning difficulties faced by UIN Mataram students were significant, as suggested by the percentage scores obtained in each category. Students from national senior high schools scored 41.7% (moderate), those from Islamic senior high schools scored 36.4% (high), and students from vocational high schools scored 16.7% (very high). The level of difficulties in learning stoichiometry was categorized as very high for students from national senior high schools in two areas: the application of Gay Lusac's law and Avogadro's hypothesis, and the application of the mole concept involving limiting reagents. The difficulties were also categorized as very high for students from Islamic senior high schools in three areas: the application of Gay Lusac's law and Avogadro's hypothesis, the application of the mole concept involving limiting reagents, and determining the compound formula. Furthermore, vocational senior high school students experienced very high difficulties in learning stoichiometry across seven topics, which included writing reaction equations, balancing reactions, formulating basic chemical laws, applying Gay Lusac's law and Avogadro's hypothesis, determining the relative equation (RE) and molecular formula (RM), applying the mole concept to limiting reagents, and determining the formula for hydrate compounds. Based on the results of this study, a differentiated learning strategy is needed to accommodate students' educational backgrounds in terms of content, process, product, and learning environment